Performance of Castor (Ricinus communis L.) Genotypes with Varying Fertility Levels under North Gujarat Agro-climatic Condition - Jat, A.L.; Parmar, L.D.; Patel, Ankit; Gangwar, G.P. (Annals of Arid Zone, 2023)
A field experiment was undertaken at Castor-Mustard Research Station, SD AU, Sardarkrushinagar, Banaskantha, Gujarat, India during kharif season of 2017. The experiment consisted eight castor hybrids (JHB 1018, SHB 974, SLCH 158, ICH 66, ICH 68, Maharaja 9, DCH 519 and GCH 7) grown with two fertility levels (100% and 125% RDF) replicated thrice in factorial randomized block design. Results revealed that the castor hybrid GCH 7 recorded tallest plant (81.6 cm), Maharaja 9 recorded higher number of nodes plant-1 (21.5), SLCH 158 registered significantly higher length of primary spike (80.5 cm) and number of capsules on primary spike (131.3). While, JHB 1018 recorded significantly higher number of effective branches plant-1 (18.8) but ICH 66 produced significantly higher 100 seed weight (33.6 g). Hybrid ICH 68 recorded significantly higher seed yield (3418 kg ha-1), Oil yield (1600 kg ha-1), crop productivity (14.8 kg ha-1 day-1), net returns (Rs. 97689 ha-1, B:C ratio (3.50) and crop profitability (Rs. 423 ha-1 day-1). Application of 125% RDF produced numerically higher seed yield and net returns but it was failed to showed significant variation. Crop productivity and profitability was unaffected due to different fertility levels but recorded numerically higher with the application of 125% RDF. Partial factor productivity has not influenced significantly due to various genotypes but it was observed significantly higher with the application of 100% RDF.